2015
DOI: 10.1902/jop.2014.140313
|View full text |Cite
|
Sign up to set email alerts
|

Postdoctoral Periodontal Program Directors’ Perspectives of Resident Selection

Abstract: This study describes the criteria used by postdoctoral periodontal programs to help select applicants. Interview ratings, dental school grades, personal statements, and letters of recommendation were found to be the most important factors. Results from this study may be helpful for prospective postdoctoral periodontal program applicants in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Khan their areas of strength and share any information that wasn't covered during the interview. 18 Faraz et al also found the essay to be an important factor in pediatric dentistry resident selection. 20 The least important factors were that the applicant is a graduate of the dental school where the program is located; ADAT scores; applicant's fluency in a second language; private practice experience; and publication or presentation in professional meetings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Khan their areas of strength and share any information that wasn't covered during the interview. 18 Faraz et al also found the essay to be an important factor in pediatric dentistry resident selection. 20 The least important factors were that the applicant is a graduate of the dental school where the program is located; ADAT scores; applicant's fluency in a second language; private practice experience; and publication or presentation in professional meetings.…”
Section: Discussionmentioning
confidence: 99%
“…7 Dental school class rank and dental school clinical grades have been important in resident selection for several different advanced dental education programs including oral and maxillofacial surgery, prosthodontics, orthodontics, endodontics, and periodontics. 6,[16][17][18][19] Many programs valued dental school grades in the specified specialty. 18,19 This study's results demonstrated that the other parts of application increased in importance and in similar rank order as compared to 2005.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations